Factors Affecting Successful Weight Loss Among Obese Persons - สุลักขณานุรักษ์ ชลวิภา; ตะสิงห์ อูน (Journal of Health Science of Thailand, 2021)
The objective of this study was to evaluate the factors that affected body transformation among obese adults who were able to lose weight and maintain weight continuously; and study the ways to prevent obesity in a sustainable manner. It was conducted as a qualitative research in Phra Nakhon Si Ayutthaya province. Data were collected by in-depth interviews with specific sampling from 12 samples; and were analyzed by content analysis. The results showed that the most common cause of obesity was the overeating of food, especially sweet beverages, sweets, fried food, and high-fat foods. Many factors that affect the body of samples made the sample lose their weight and could control their weight successfully. The long-term care of obesity included diet control, exercise, attitude adjustment, lifestyle and nutritional habits changes, increased happiness, stress management, self-confidence, and not to compare with others. These approaches should be performed relularly with discipline in order to ontrol weight successfully. If any action is missing, it may affect obesity management in the long term and may lead to obesity recurrence.